Genetics and physiology of cell wall polysaccharides in the model C4 grass, Setaria viridis spp. Issue 1 (December 2015) - Ermawar, Riksfardini; Collins, Helen; Byrt, Caitlin; Henderson, Marilyn; O'Donovan, Lisa; Shirley, Neil; Schwerdt, Julian; Lahnstein, Jelle; Fincher, Geoffrey; Burton, Rachel
Abstract Background Setaria viridis has emerged as a model species for the larger C4 grasses. Here thecellulose synthase (CesA ) superfamily has been defined, with an emphasis on the amounts and distribution of (1, 3;1, 4)-β-glucan, a cell wall polysaccharide that is characteristic of the grasses and is of considerable value for human health. Methods Orthologous relationship of theCesA and Poales-specificcellulose synthase-like (Csl ) genes amongSetaria italica (Si ), Sorghum bicolor (Sb ), Oryza sativa (Os ), Brachypodium distachyon (Bradi ) andHordeum vulgare (Hv ) were compared using bioinformatics analysis. Transcription profiling ofCsl gene families, which are involved in (1, 3;1, 4)-β-glucan synthesis, was performed using real-time quantitative PCR (Q-PCR). The amount of (1, 3;1, 4)-β-glucan was measured using a modified Megazyme assay. The fine structures of the (1, 3;1, 4)-β-glucan, as denoted by the ratio of cellotriosyl to cellotetraosyl residues (DP3:DP4 ratio) was assessed by chromatography (HPLC and HPAEC-PAD). The distribution and deposition of the MLG was examined using the specific antibody BG-1 and captured using fluorescence and transmission electron microscopy (TEM). Results The cellulose synthase gene superfamily contains 13CesA and 35Csl genes inSetaria . Transcript profiling ofCslF, CslH andCslJ gene families across a vegetative tissue series indicated thatSvCslF6 transcripts were the most abundant relative to all otherCsl transcripts. The amounts of (1, 3;1, 4)-β-glucan inSetaria vegetative tissues ranged from 0.2% to 2.9% w/w with much smaller amounts in developing grain (0.003% to 0.013% w/w). In general, the amount of (1, 3;1, 4)-β-glucan was greater in younger than in older tissues. The DP3:DP4 ratios varied between tissue types and across developmental stages, and ranged from 2.4 to 3.0:1. The DP3:DP4 ratios in developing grain ranged from 2.5 to 2.8:1. Micrographs revealing the distribution of (1, 3;1, 4)-β-glucan in walls of different cell types and the data were consistent with the quantitative (1, 3;1, 4)-β-glucan assays. Conclusion The characteristics of thecellulose synthase gene superfamily and the accumulation and distribution of (1, 3;1, 4)-β-glucans inSetaria are similar to those in other C4 grasses, including sorghum. This suggests thatSetaria is a suitable model plant for cell wall polysaccharide biology in C4 grasses.